Developing mathematical understanding and students with emotional and behavioural disorders: a review of the literature. Issue 4 (1st October 2016) - Tan, Paulo
ABSTRACT: Recent shifts in focus on academic interventions for students diagnosed with emotional and behavioural disorders (EBD) create a need to evaluate existing interventional research in content areas such as mathematics. Literature reviews in the area of mathematics interventions for students with EBD have mostly focused on the outcomes and the rigour of existing studies with limited attention to the quality of the pedagogical methods used in those studies. The purpose of this conceptual review was to use a teaching-for-understanding lens to examine existing research interventions in mathematics for students with EBD. Teaching-mathematics-for-understanding requires pedagogical methods that aim to activate and capture students' mathematical reasoning and thinking. An iterative electronic and hand search of the literature found 30 studies covering three decades (1985–2015) that met the criteria for inclusion in this review. Results of the analysis include: (1) mathematics assessments utilised ranged from very basic to comprehensive, with most studies applying basic assessments; (2) a majority of the studies focused on intervention strategies targeting procedural and rote knowledge; (3) most studies utilised quantitative inquiry methods; and (4) in more recent years, studies have increasingly examined conceptual mathematical understanding and incorporated qualitative inquiry methods.